Effect of corn steep liquor on lettuce root rot (Fusarium oxysporum f.sp. lactucae) in hydroponic cultures. (14th February 2014) - Chinta, Yufita D; Kano, Kazuki; Widiastuti, Ani; Fukahori, Masaru; Kawasaki, Shizuka; Eguchi, Yumi; Misu, Hideyuki; Odani, Hiromitsu; Zhou, Songying; Narisawa, Kazuhiko; Fujiwara, Kazuki; Shinohara, Makoto; et al.
Abstract BACKGROUND Recent reports indicate that organic fertilisers have a suppressive effect on the pathogens of plants grown under hydroponic systems. Furthermore, microorganisms exhibiting antagonistic activity to diseases have been observed in organic hydroponic systems. This study evaluated the effect of corn steep liquor (CSL) on controlling lettuce root rot disease [Fusarium oxysporum f.sp. lactucae (FOL)] in a hydroponic system. The effect of CSL and Otsuka A (a chemical fertiliser) on the inhibition of FOL in terms of mycelial growth inhibition was tested in vivo. RESULTS Addition of CSL suppressed FOL infection rates. CSL inhibited FOL infection by 26.3–42.5% from 2 days after starting incubation. In comparison, Otsuka A inhibited FOL growth by 5.5–19.4%. In addition, four of 10 bacteria isolated from the nutrient media containing CSL exhibited inhibition zones preventing FOL mycelial growth. CONCLUSIONS We found that CSL suppressed FOL in lettuce via its antifungal and biostimulatory effects. We suggest that activation of beneficial microorganisms present in CSL may be used to decrease lettuce root rot disease and contribute to lettuce root growth. © 2014 Society of Chemical Industry